Mycobacterium chelonae cutaneous infection: An opportunistic disease in an immunosuppressed patient with myasthenia gravis. (2020) - Granado, Joana; Miranda, Ana Cláudia; Fernandes, Marco; Santos, Luís; Mansinho, Kamal
Highlights: Mycobacterium chelonae infection may occur in chronic treatment with steroids. The most common presentation form is disseminated cutaneous infection. First-line treatment should be a triple antibiotics association for at least 4 months. Macrolides, fluoroquinolones and other antibiotics may exacerbate myasthenia gravis. Abstract: Mycobacterium chelonae can cause chronic skin, soft-tissue or bone infections. and is often associated with the immunocompromised state.We describe a case of a 58-year-old male patient with myasthenia gravis, chronically immunosuppressed, with a four month progression of growing erythematous, nodular and hard cutaneous lesions in the left forearm, leg and foot. He was receiving immunoglobulin every four weeks (2 g/kg) and prednisolone 25 mg/day and had an important previous history of several opportunistic infections while he was receiving corticosteroids. Histopathological examination of a biopsy showed acid-fast bacilli and tissue culture identified a Mycobacterium spp. within seven days of incubation, with Mycobacterium chelonae being identified by polymerase chain reaction assay. Antimicrobial susceptibility testing was performed showing no resistance and the patient was successfully treated during four months with ciprofloxacin, clarithromycin and trimethoprim-sulfamethoxazole with regression of the lesions, leaving some hyperpigmentation scars and without unbalancing his neurological disease. Patients with myasthenia gravis should be closely monitored because first line treatments for M. chelonae infection may be associated with myasthenic crisis.